Ischemic stroke in a young patient with Fahr's disease: a case report. Issue 1 (December 2016) - Yang, Chih-Sheng; Lo, Chung-Ping; Wu, Man-Chun
Abstract Background Fahr's disease is a rare neurodegenerative disorder characterized by diffuse intracranial calcium deposition and associated cell loss mainly in bilateral basal ganglia and dentate nuclei of the cerebellum. Subarachnoid hemorrhage and epileptic syncope had been reported as acute presentation of Fahr's disease. We here report a 36-year-old male Indonesian diagnosed as Fahr's disease presenting with young-onset ischemic stroke. Case presentation A 36-year-old male Indonesian without prior systemic disease or neurologic disorder presented with young-onset ischemic stroke involving the right posterior limb of internal capsule. Brain computed tomography and magnetic resonance imaging demonstrated symmetric calcifications in bilateral basal ganglia, internal capsules, cerebellar dentate nuclei, thalami, cerebral white matter, which were all consistent with Fahr's disease. The laboratory studies excluded the presence of other pathologic processes leading to secondary intracranial calcification. Other young stroke surveys were unremarkable. After medical treatment and sustained physical rehabilitation for 3 months, he recovered to carry out daily activities independently. Conclusion We present ischemic stroke in a young patient with sporadic Fahr's disease. The differentiation between Fahr's disease and Fahr's syndrome is specially highlighted when brain CT exhibits diffuse, symmetric calcifications in bilateral basal ganglia, thalami, cerebellar dentate nuclei and cerebral white matter. The association between nonarteriosclerotic vascular calcification and cerebrovascular disease is worth special attention and further investigation.